High-temperature-resistant filter cloth material and preparation method thereof
By employing a sandwich structure of PI microfiber mesh and glass fiber woven fabric in the filter cloth material, the problems of low mechanical strength and poor filtration effect under high temperature environment are solved, achieving high-efficiency filtration of small-diameter dust and high-temperature resistance.
Patent Information
- Application Number
- CN202511051178.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-07-29
- Publication Date
- 2025-11-07
- Estimated Expiration
- 2045-07-29
AI Technical Summary
Existing industrial filter cloths have low mechanical strength under high temperature conditions, are prone to wear and breakage, and are not effective at filtering small-diameter dust particles.
The material adopts a sandwich structure design, with a PI microfiber mesh layer in the middle and glass fiber woven fabric on both sides. PAA nanofiber membranes are prepared by electrospinning and subjected to gradient heating treatment to form a high-temperature resistant filter cloth material.
The mechanical strength and abrasion resistance of the filter cloth have been improved, enabling it to efficiently intercept small-diameter dust particles and making it suitable for industrial dust removal in high-temperature environments.
Abstract
Description
TECHNICAL FIELD
[0001] The application belongs to the technical field of filter cloth materials, and particularly relates to a high-temperature-resistant filter cloth material and a preparation method thereof. BACKGROUND
[0002] Industrial filter cloth is a filter medium woven from natural fibers and synthetic fibers, and is mainly used for solid-liquid separation, gas-solid separation and industrial dust removal; the existing synthetic fibers for industrial filter cloth mainly include polypropylene, polyester, nylon and vinylon, among which, polyester and polypropylene are most commonly used, and solid-liquid separation is mainly used, and the general industrial filter cloth also includes various metal material woven meshes such as stainless steel wire, nickel wire and brass wire. The weaving methods include plain weaving, twill weaving and satin weaving, and non-woven needle punching forming. The industrial filter cloth has the characteristics of high precision, high load, acid resistance, alkali resistance, temperature resistance, wear resistance and special filtering performance. However, the existing industrial filter cloth often works in a complex and harsh environment, and the mechanical strength of the industrial filter cloth is not high. If the strength of the industrial filter cloth is not high, the service life is greatly shortened.
[0003] Glass fiber is an inorganic non-metallic material with excellent performance. It is made of glass balls or waste glass as raw materials through high-temperature melting, wire drawing, winding and weaving processes, and the diameter of the single fiber is several microns to twenty microns. Each bundle of fiber filaments is composed of hundreds or even thousands of single fibers. High strength is the outstanding advantage of glass fiber, and the high strength makes glass fiber widely used. However, glass fiber also has obvious disadvantages, such as brittleness, poor folding resistance and poor wear resistance. In the process of use, the glass fiber is frequently cleaned, which is easy to wear and break, and affects the service life.
[0004] Therefore, there is an urgent need in the existing market to seek a filter cloth with high strength, wear resistance and long service life. At present, polytetrafluoroethylene (PTFE) fiber filter material, polyphenylene sulfide (PPS) fiber filter material, glass fiber filter material, ceramic fiber filter material and metal fiber filter material are used. However, the fiber diameter of these traditional filter materials is large, and the pore size of the fabric is also large, so there is almost no filtering effect on small particle size dust particles. Therefore, this type of filter material cannot meet the current dust removal standard. SUMMARY
[0005] The purpose of the present application is to provide a high-temperature-resistant filter cloth material and a preparation method thereof. The PI ultra-fine fiber net layer in the middle and the glass fiber woven fabric on both sides form a sandwich structure. The diameter of the PI ultra-fine fiber net layer is in the nanometer level, which can efficiently intercept some small particle size dust particles. The glass fiber woven fabric not only serves as an outer reinforcing material, but also provides a pre-filtering effect for the filter cloth. Large particle size dust particles are first intercepted, and the sandwich structure works together to improve the filtering effect.
[0006] The purpose of the present application can be achieved by the following technical solutions:
[0007] The application discloses a preparation method of a high-temperature-resistant filter cloth material.
[0008] Step one: anhydride-modified silsesquioxane is obtained by copolymerization of octaalkenyl silsesquioxane, alkenyl succinic anhydride and diethylene glycol divinyl ether under the action of benzoyl peroxide.
[0009] Step two: a silsesquioxane-modified polyamide acid solution is obtained by using octaalkenyl silsesquioxane, 4,4'-oxybisphthalic anhydride, 1,3-bis(4'-aminophenoxy) benzene and 3,5-diaminobenzoic acid as raw materials and N-methyl-2-pyrrolidone as a solvent.
[0010] Step three: PAA nanofiber membrane is obtained by electrospinning of the silsesquioxane-modified polyamide acid solution.
[0011] Step four: glass fiber woven fabric is used as the reinforcing layer of the upper layer and the lower layer respectively, and the PAA nanofiber membrane is used as the middle layer to be stitched, and then gradient temperature treatment is carried out, so that a "sandwich structure" composite filter material composed of the upper reinforcing layer, the middle PI ultrafine net filter layer and the lower reinforcing layer is formed, and the high-temperature-resistant filter cloth material is obtained.
[0012] Further, the preparation steps of the anhydride-modified silsesquioxane are as follows:
[0013] Octaalkenyl silsesquioxane and dichloromethane are poured into a four-necked flask provided with a rotating vane impeller, a reflux condenser, a thermometer and a nitrogen inlet, stirring is carried out under the protection of nitrogen at 20-25 DEG C and 500-600 r / min for 20-30 min, heating is carried out to 80-90 DEG C, then benzoyl peroxide, alkenyl succinic anhydride and diethylene glycol divinyl ether are added, and stirring is continuously carried out for 4-5 h, and the solvent is removed by rotary evaporation, so that the anhydride-modified silsesquioxane is obtained.
[0014] Further, the dosage ratio of octaalkenyl silsesquioxane, dichloromethane, benzoyl peroxide, alkenyl succinic anhydride and diethylene glycol divinyl ether is 20-30 g:90-100 g:1-2 g:20-25 g:3-5 g.
[0015] Further, the preparation steps of the silsesquioxane-modified polyamide acid solution are as follows:
[0016] 4,4'-oxydiphthalic anhydride and 1,3-bis(4'-aminophenoxy)benzene, 3,5-diaminobenzoic acid, and N-methyl-2-pyrrolidone are added into a reaction kettle, stirred at 0-4℃ and 500-600r / min under nitrogen protection for 20-30min, then heated to 20-25℃, continue to stir for 4-5h, then add anhydride modified silsesquioxane, continue to stir for 10-12h, to obtain a silsesquioxane modified polyamic acid solution.
[0017] Further, the use amount ratio of 4,4'-oxydiphthalic anhydride, 1,3-bis(4'-aminophenoxy)benzene, 3,5-diaminobenzoic acid, N-methyl-2-pyrrolidone and anhydride modified silsesquioxane is 130-140g: 120-130g: 50-60g: 800-900mL: 80-90g.
[0018] Further, the specific preparation steps of the PI ultrafine fiber web layer are as follows:
[0019] The silsesquioxane modified polyamic acid solution is diluted into a silsesquioxane modified polyamic acid diluent, then the diluent is respectively subjected to magnetic stirring for 24-26h and ultrasonic dispersion for 1-2h, an appropriate amount of diluent is carefully sucked with a syringe needle, a needle (21G) is fixed on the syringe pump for spinning, the output voltage of the high-voltage power supply is 11-13kV, the rotation speed of the collection roller is 5-7r / min, the anode of the high-voltage power supply is loaded on the needle, the collection roller is grounded, the output voltage of the high-voltage power supply is adjusted and spinning is started, a layer of milky white PAA nanofiber membrane is collected on the collection device, the milky white PAA nanofiber membrane is dried at 80-90℃ for 6-7h to remove residual solvent, and a PAA nanofiber membrane is obtained.
[0020] Further, the mass concentration of the silsesquioxane modified polyamic acid diluent is 12wt%-14wt%.
[0021] Further, the gradient temperature treatment is then heated to 100-110℃, 200-210℃, 300-310℃, 350-360℃, and the temperature of each stage is maintained for 30-50min,
[0022] Further, the specific preparation steps of the high-temperature-resistant filter cloth material are as follows:
[0023] The polyimide yarn is used to stitch the receiving layer glass fiber woven fabric, PAA nanofiber membrane and glass fiber woven fabric in the direction of vertical plane, finally forming a "sandwich structure" composite filter material composed of an upper reinforcing layer, a middle PI ultrafine fiber web filter layer and a lower reinforcing layer, and then gradient temperature treatment is carried out, so that the PAA nanofiber web is subjected to gradient heat ring-opening reaction, and a high-temperature-resistant filter cloth material is obtained.
[0024] Further, the glass fiber woven fabric is double twill cloth, and the weight is 780 g / m 2 .
[0025] Further, the application further provides a high-temperature-resistant filter cloth material obtained by the preparation method of the high-temperature-resistant filter cloth material.
[0026] The application has the following beneficial effects:
[0027] 1. The high-temperature-resistant filter cloth material forms a sandwich structure, the middle is a PI ultrafine fiber web layer, and both sides are glass fiber woven fabrics. In a high-temperature environment, the PI ultrafine fiber web layer is treated in a special way, which can avoid the interface delamination, debonding or interface fracture caused by the different thermal expansion and cold shrinkage coefficients of the layers, which further causes the overall performance of the composite material to be damaged, especially the decline of the filtration performance and mechanical strength, and has good filtering effect when applied to industrial dust removal, and has excellent strength, toughness and high-temperature resistance.
[0028] 2. The PI ultrafine fiber web layer is modified by polysilsesquioxane on the polyamide acid main chain, and then is subjected to stepwise heat ring-opening. The POSS structure itself has high thermal stability, and when it is successfully doped or grafted to the PI main chain or side chain, the decomposition temperature and carbon residue rate of the PI material can be significantly improved, which is helpful for the long-term service of the material in a high-temperature environment. After the rigid cage structure of POSS is added, the PI chain segment movement is limited, the flexibility of the molecular chain is reduced, and the linear thermal expansion coefficient (CTE) of the polyimide material is reduced, which is particularly important for the precision field such as electronic device packaging. The inorganic cage structure of POSS enhances the overall rigidity of the material, but excessive addition will increase the brittleness of the material itself, reduce the elongation rate and fracture toughness. Therefore, by grafting copolymerization, the performance balance can be realized, and appropriate introduction of POSS can increase the modulus and strength of polyimide, avoid the compatibility problem and self-aggregation caused by traditional direct addition, and reduce the mechanical properties caused by uneven dispersion or high doping ratio.
[0029] 3. The diameter of the PI ultra-fine fiber web layer is in the nanometer level, which can effectively intercept some small particle dust particles, avoid the large fiber diameter of the traditional filter material and the large pore size of the fabric, resulting in low filtration degree, and by forming a sandwich structure, the glass fiber woven fabric as the outer layer reinforcing material can isolate part of the heat radiation, protect the PI ultra-fine fiber web layer from direct heat shock in high-temperature flue gas, and the PI ultra-fine fiber web layer maintains the filtration layer form through the rigid structure of the molecular chain, avoiding the micro-crack expansion of the glass fiber due to brittleness. DETAILED DESCRIPTION
[0030] The technical solutions in the embodiments of the present application will be clearly and completely described below in combination with the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, rather than all the embodiments. Based on the embodiments in the present application, all other embodiments obtained by those skilled in the art without creative labor fall within the scope of protection of the present application.
[0031] In the specific embodiment of the present application, the glass fiber woven fabric is a double twill fabric, and the weight is 780 g / m 2 .
[0032] Embodiment 1: A preparation method of a high-temperature-resistant filter cloth material, comprising the following steps:
[0033] S1: 20 g of octaalkylsilsesquioxane and 90 g of dichloromethane are poured into a four-necked flask equipped with a rotating blade impeller, a reflux condenser, a thermometer and a nitrogen inlet, stirred at 20℃ and 500 r / min for 20 min under nitrogen protection, heated to 80℃, then 1 g of benzoyl peroxide, 20 g of alkenyl succinic anhydride and 3 g of diethylene glycol divinyl ether are added, and the reaction is continued for 4 h, and the solvent is removed by rotary evaporation to obtain anhydride-modified silsesquioxane.
[0034] S2: 130 g of 4,4'-oxybisphthalic anhydride and 120 g of 1,3-di(4'-aminophenoxy)benzene, 50 g of 3,5-diaminobenzoic acid and 800 mL of N-methyl-2-pyrrolidone are added to a reaction kettle, stirred at 0℃ and 500 r / min for 20 min under nitrogen protection, then heated to 20℃, continue to stir for 4 h, then add 80 g of anhydride-modified silsesquioxane, continue to stir for 10 h, and obtain a silsesquioxane-modified polyamide acid solution.
[0035] S3: The silyl modified polyamide acid solution was diluted to a mass concentration of 12wt% silyl modified polyamide acid diluent, then the diluent was subjected to magnetic stirring for 24h, ultrasonic dispersion for 1h, and a suitable amount of diluent was carefully sucked up with a syringe needle, a needle (21G) was installed and fixed on the syringe pump for spinning, the spinning was carried out under the conditions of a syringe pump extrusion rate of 0.2mL / h, an output voltage of the high-voltage power supply of 11kV, and a rotating speed of the collection roller of 5r / min, the anode of the high-voltage power supply was loaded on the needle, the collection roller was grounded, the output voltage of the high-voltage power supply was adjusted and the spinning was started, a layer of milky white PAA nanofiber membrane was collected on the collection device, the milky white PAA nanofiber membrane was dried at 80℃ for 6h to remove residual solvent, and a PAA nanofiber membrane was obtained.
[0036] S4: The receiving layer glass fiber woven fabric, the PAA nanofiber membrane and the glass fiber woven fabric were stitched in the direction perpendicular to the plane using polyimide yarn, and finally a "sandwich structure" composite filter material composed of an upper reinforcing layer, a middle PI ultrafine web filter layer and a lower reinforcing layer was formed, and then heated to 110℃, 210℃, 310℃ and 360℃, respectively, and each stage was kept at temperature for 40min, and the PAA nanoweb was subjected to gradient heat ring-opening reaction to obtain a high-temperature-resistant filter cloth material.
[0037] Example 2: A method for preparing a high-temperature-resistant filter cloth material, comprising the following steps:
[0038] S1: 25g of octaalkenyl silyl and 95g of dichloromethane were poured into a four-necked flask equipped with a rotating blade impeller, a reflux condenser, a thermometer and a nitrogen inlet, stirred at 22.5℃ and 550r / min for 25min under nitrogen protection, heated to 85℃, then 1.5g of benzoyl peroxide, 22g of alkenyl succinic anhydride and 4g of diethylene glycol divinyl ether were added, and the stirring was continued for 4.5h, and the solvent was removed by rotary evaporation to obtain an anhydride modified silyl.
[0039] S2: 135g of 4,4'-oxybisphthalic anhydride and 125g of 1,3-di(4'-aminophenoxy)benzene, 55g of 3,5-diaminobenzoic acid and 850mL of N-methyl-2-pyrrolidone were added to a reaction kettle, stirred at 2℃ and 550r / min for 25min under nitrogen protection, then heated to 22.5℃, and the stirring was continued for 4.5h, then 85g of anhydride modified silyl was added, and the stirring was continued for 11h to obtain a silyl modified polyamide acid solution.
[0040] S3: The silsesquioxane-modified polyamic acid solution was diluted to a mass concentration of 13wt% to obtain a silsesquioxane-modified polyamic acid diluent, and then the diluent was subjected to magnetic stirring for 25h and ultrasonic dispersion for 1.5h. An appropriate amount of the diluent was carefully sucked into a syringe needle, a needle (21G) was mounted and fixed on a syringe pump for spinning. The spinning was performed under the conditions of a syringe pump extrusion rate of 0.3mL / h, an output voltage of a high-voltage power supply of 12kV, and a rotating speed of a collection roller of 6r / min. The anode of the high-voltage power supply was loaded onto the needle, the collection roller was grounded, the output voltage of the high-voltage power supply was adjusted, and the spinning was started. A layer of milky white PAA nanofiber membrane was collected on the collection device. The milky white PAA nanofiber membrane was dried at 85℃ for 6.5h to remove residual solvents, and a PAA nanofiber membrane was obtained.
[0041] S4: The receiving layer glass fiber woven fabric, the PAA nanofiber membrane, and the glass fiber woven fabric were stitched using polyimide yarns in the direction perpendicular to the plane, and finally a "sandwich structure" composite filter material composed of an upper reinforcing layer, a middle PI ultrafine web filter layer, and a lower reinforcing layer was formed. Then, the material was heated to 110℃, 210℃, 310℃, and 360℃, respectively, and each temperature was maintained for 40min. Gradient temperature treatment was performed to make the PAA nanoweb undergo a gradient thermal ring-opening reaction, and a high-temperature-resistant filter cloth material was obtained.
[0042] Example 3: A method for preparing a high-temperature-resistant filter cloth material, comprising the following steps:
[0043] S1: 30g of octaalkenylsilsesquioxane and 100g of dichloromethane were poured into a four-necked flask equipped with a rotating vane impeller, a reflux condenser, a thermometer, and a nitrogen inlet. The mixture was stirred at 25℃ and 600r / min for 30min under nitrogen protection, and then heated to 90℃. Then, 2g of benzoyl peroxide, 25g of alkenyl succinic anhydride, and 5g of diethylene glycol divinyl ether were added, and the reaction was continued for 5h while stirring. The solvent was removed by rotary evaporation to obtain anhydride-modified silsesquioxane.
[0044] S2: 140g of 4,4'-oxybisphthalic anhydride and 130g of 1,3-di(4'-aminophenoxy)benzene, 60g of 3,5-diaminobenzoic acid, and 900mL of N-methyl-2-pyrrolidone were added to a reaction kettle. The mixture was stirred at 4℃ and 600r / min for 30min under nitrogen protection, and then heated to 25℃. The stirring was continued for 5h, and then 90g of anhydride-modified silsesquioxane was added. The stirring was continued for 12h to obtain a silsesquioxane-modified polyamic acid solution.
[0045] S3: The silsesquioxane modified polyamic acid solution was diluted to a mass concentration of 14wt% silsesquioxane modified polyamic acid diluent, respectively, and then the diluent was subjected to magnetic stirring for 26h and ultrasonic dispersion for 2h. An appropriate amount of diluent was carefully sucked with a syringe needle, a needle (21G) was installed and fixed on the syringe pump for spinning. The spinning was carried out under the conditions of an injection pump extrusion rate of 0.4mL / h, an output voltage of a high-voltage power supply of 13kV, and a rotating speed of a collection roller of 7r / min. The anode of the high-voltage power supply was loaded on the needle, the collection roller was grounded, the output voltage of the high-voltage power supply was adjusted and the spinning was started. A layer of milky white PAA nanofiber membrane was collected on the collection device. The milky white PAA nanofiber membrane was dried at 90℃ for 7h to remove residual solvent, and a PAA nanofiber membrane was obtained.
[0046] S4: The receiving layer glass fiber woven fabric, the PAA nanofiber membrane and the glass fiber woven fabric were stitched in the direction perpendicular to the plane using polyimide yarns, and finally a "sandwich structure" composite filter material composed of an upper reinforcing layer, a middle PI ultrafine web filter layer and a lower reinforcing layer was formed. Then, heating was carried out to 110℃, 210℃, 310℃ and 360℃, respectively, and each stage was kept at temperature for 40min. Gradient temperature treatment was carried out to make the PAA nanoweb undergo gradient thermal cyclization reaction, and a high-temperature-resistant filter cloth material was obtained.
[0047] Comparative Example 1: On the basis of Example 3, the octavinyl silsesquioxane in step S1 was removed.
[0048] Comparative Example 2: On the basis of Example 3, the anhydride modified silsesquioxane in step S2 was replaced by the octavinyl silsesquioxane in step S1.
[0049] Comparative Example 3: On the basis of Example 3, the diethylene glycol divinyl ether in step S1 was removed, and the silsesquioxane was directly connected to the polyimide main chain only through the anhydride group.
[0050] The high-temperature-resistant filter cloth materials obtained in Examples 1-3 and Comparative Examples 1-3 were tested for performance, and the results are shown in Table 1:
[0051] 1. Filtration efficiency test: According to the test standard of GB / T 6165-2021 "Performance test method for high efficiency air filter efficiency and resistance", 0.3μm standard dust (NaCl aerosol) was used, the concentration difference before and after filtration was measured by particle counter, and the efficiency was calculated.
[0052] 2. Strength test: According to the test standard of GB / T 7689.5-2013 "Test method for tensile strength of woven fabric of reinforced material", 250mm×25mm sample was used, tensile rate was 10mm / min, and longitudinal breaking strength was recorded.
[0053] 3. Elongation at break test: Refer to the test standard of GB / T 7689.5-2013, synchronously with the strength test, record the elongation at break.
[0054] 4. Temperature resistance test: Refer to the test standard of HJ / T 324-2006, the test temperature is 200℃, heat the filter material sample at the set high temperature, measure the breaking strength after heating for 100h, and compare with the breaking strength of the original unheated sample, calculate the strength retention rate:
[0055] Table 1 Performance test table of high temperature resistant filter cloth material
[0056] Item Example 1 Example 2 Example 3 Comparative Example 1 Comparative Example 2 Comparative Example 3 Filtering efficiency (%) 99.3 99.5 99.8 81.2 82.9 71.3 Strength (CN) 473 482 493 401 416 379 Elongation at break (%) 44.8 46.5 48.2 32.6 33.8 27.5 Temperature resistance (%) 91.6 92.5 93.5 78.3 76.5 65.3
[0057] As can be seen from Table 1, the filtration efficiency, strength and elongation at break of the high temperature resistant filter cloth material obtained by Examples 1-3 are significantly better than those of the comparative examples, which shows that the high temperature resistant filter cloth material prepared by the application has good filtering effect when applied to industrial dust removal, and at the same time has excellent strength, toughness and high temperature resistance.
[0058] In Comparative Example 1, the octaalkenyl silsesquioxane is removed, the octaalkenyl POSS is directly discarded in the S1 step, and only the alkenyl succinic anhydride and diethylene glycol divinyl ether are used for reaction. The cage type siloxane structure of POSS can improve the high temperature resistance of polyimide. After being discarded, the PI ultrafine web layer may be broken at a molecular chain at 300℃ or above, resulting in easy softening and deformation of the filter cloth in high temperature flue gas, loss of filtering performance. The rigid cage structure of POSS can inhibit the thermal motion of PI segments and reduce the CTE. After being lost, the difference in thermal expansion between the PI layer and the glass fiber layer increases, the interface is easy to delaminate, and the filter cloth fails in advance under alternating hot and cold conditions. POSS enhances the intermolecular force of PI by grafting, thereby improving the breaking strength. After being discarded, the brittleness of the nanofiber membrane increases, and the blowing of the ash removal gas flow may cause the web to break.
[0059] In Comparative Example 2, the anhydride modified silsesquioxane is replaced by octaalkenyl silsesquioxane. The active groups of the anhydride modified POSS can react with the amine groups of the polyamide acid to form chemical bonds, ensuring uniform dispersion. The alkenyl group of the unmodified POSS cannot react with the polyamide acid, resulting in agglomeration of the POSS in the solution. The inert surface of the unmodified POSS cannot participate in the imidization reaction. When the temperature is gradually increased, micropores are generated between the POSS and the polyimide matrix, reducing the fiber density. The agglomerated POSS becomes a stress concentration point, resulting in a decrease in the breaking strength of the PI ultrafine web layer.
[0060] The unmodified POSS surface is a rigid cage structure in Comparative Example 3, and when directly bonded with the polyimide chain, stress concentration points are formed at the interface due to large modulus difference, and micro-cracks are easily induced under external force. Diethylene glycol divinyl ether can impart flexibility to the rigid cage structure. Without flexible chain buffering, POSS acts as a rigid point to hinder dislocation slip, and the material elongation at break decreases significantly.
[0061] While the embodiments of the application have been illustrated and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and alterations can be made therein without departing from the principles and spirit of the application.
Claims
1. A method for producing a high-temperature resistant filter cloth material, characterized by, Comprising the following steps: Step one: by octaalkenyl silsesquioxane, alkenyl succinic anhydride and diethylene glycol divinyl ether under the action of benzoyl peroxide copolymerization, anhydride modified silsesquioxane is obtained; Step two: by anhydride modified silsesquioxane, 4,4'-oxybisphthalic anhydride, 1,3-bis(4'-aminophenoxy)benzene and 3,5-diaminobenzoic acid as raw material, N-methyl-2-pyrrolidone as solvent to obtain silsesquioxane modified polyamide acid solution; Step three: the silsesquioxane modified polyamide acid solution is obtained by electrospinning to obtain PAA nanofiber membrane; Step four: the glass fiber woven fabric is respectively used as the outer layer and the bottom layer of the reinforcing layer, and the PAA nanofiber membrane is used as the middle layer to be stitched, and then gradient temperature treatment is carried out to obtain a high-temperature-resistant filter cloth material.
2. The method for preparing a high-temperature resistant filter cloth material according to claim 1, characterized in that, The specific preparation steps of the anhydride modified silsesquioxane are as follows: The octaalkenyl silsesquioxane and dichloromethane are poured into a four-necked flask equipped with rotating blade impeller, reflux condenser, thermometer and nitrogen inlet, stirred at 20-25℃ and 500-600r / min for 20-30min under nitrogen protection, heated to 80-90℃, then benzoyl peroxide, alkenyl succinic anhydride and diethylene glycol divinyl ether are added, continue to stir for 4-5h, remove the solvent by rotary evaporation to obtain anhydride modified silsesquioxane.
3. The method for preparing a high-temperature resistant filter cloth material according to claim 2, characterized in that, The amount ratio of octaalkenyl silsesquioxane, dichloromethane, benzoyl peroxide, alkenyl succinic anhydride and diethylene glycol divinyl ether is 20-30g:90-100g:1-2g:20-25g:3-5g.
4. The method for preparing a high-temperature resistant filter cloth material according to claim 1, characterized in that, The specific preparation steps of the silsesquioxane modified polyamide acid solution are as follows: 4,4'-oxybisphthalic anhydride and 1,3-bis(4'-aminophenoxy)benzene, 3,5-diaminobenzoic acid and N-methyl-2-pyrrolidone are added to the reaction kettle, stirred at 0-4℃ and 500-600r / min for 20-30min under nitrogen protection, then heated to 20-25℃, continue to stir for 4-5h, then add anhydride modified silsesquioxane, continue to stir for 10-12h, to obtain silsesquioxane modified polyamide acid solution.
5. The method for preparing a high-temperature resistant filter cloth material according to claim 4, characterized in that, The amount ratio of 4,4'-oxybisphthalic anhydride, 1,3-bis(4'-aminophenoxy)benzene, 3,5-diaminobenzoic acid, N-methyl-2-pyrrolidone and anhydride modified silsesquioxane is 130-140g:120-130g:50-60g:800-900mL:80-90g.
6. The method for preparing a high-temperature resistant filter cloth material according to claim 1, characterized in that, The specific preparation steps of the PI ultrafine fiber web layer are as follows: The silsesquioxane modified polyamic acid solution is diluted into silsesquioxane modified polyamic acid diluent respectively, then the diluent is respectively subjected to magnetic stirring for 24-26h, ultrasonic dispersion for 1-2h, a proper amount of diluent is carefully sucked by a syringe needle tube, the needle head is fixed on the syringe pump for spinning, spinning is carried out under the conditions that the extrusion rate of the syringe pump is 0.2-0.4mL / h, the output voltage of the high-voltage power supply is 11-13kV, and the rotating speed of the collection roller is 5-7r / min, the anode of the high-voltage power supply is loaded to the needle head, the collection roller is grounded, the output voltage of the high-voltage power supply is adjusted and spinning is started, a layer of milky white PAA nanofiber membrane is collected on the collection device, the milky white PAA nanofiber membrane is dried at 80-90℃ for 6-7h to remove residual solvent, and a PAA nanofiber membrane is obtained.
7. The method for preparing a high-temperature resistant filter cloth material according to claim 6, characterized in that, The mass concentration of the silsesquioxane modified polyamic acid diluent is 12wt%-14wt%.
8. The method for preparing a high-temperature resistant filter cloth material according to claim 6, characterized in that, The gradient temperature treatment is then heated to 100-110℃, 200-210℃, 300-310℃, 350-360℃, and the temperature of each stage is maintained for 30-50min.
9. The method for preparing a high-temperature resistant filter cloth material according to claim 1, characterized in that, The preparation steps of the high-temperature-resistant filter cloth material are as follows: The receiving layer glass fiber woven fabric, the PAA nanofiber membrane and the glass fiber woven fabric are stitched in the direction perpendicular to the plane by using polyimide yarn, finally forming a "sandwich structure" composite filter material composed of an upper reinforcing layer, a middle PI ultrafine net filter layer and a lower reinforcing layer, the gradient temperature treatment is carried out to make the PAA nanofiber net undergo gradient heat ring-opening reaction, and a high-temperature-resistant filter cloth material is obtained.
10. A high temperature resistant filter cloth material, characterized in that, The high-temperature-resistant filter cloth material is prepared by the method of any one of claims 1-9. The high-temperature-resistant filter cloth material is prepared by the method of any one of claims 1-9.
Citation Information
Patent Citations
Multi-scale fiber composite filter material and preparation method thereof
CN104524867A
Electrostatic spinning method and nanometer fiber / anti-sticking non-woven fabric composite filter material prepared through electrostatic spinning method
CN105200539A
High-temperature-resistant anti-corrosion flame-retardant filter material as well as preparation method and application thereof
CN116747609A
High-toughness and friction-resistant polyimide micro-nano fiber filter material and preparation method thereof
CN118236865A
Filter material and method of making a filter material
EP0829293A1